2016
DOI: 10.7554/elife.13446
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PTHrP-cAMP-CREB1 signaling following p53 loss is essential for osteosarcoma initiation and maintenance

Abstract: Mutations in the P53 pathway are a hallmark of human cancer. The identification of pathways upon which p53-deficient cells depend could reveal therapeutic targets that may spare normal cells with intact p53. In contrast to P53 point mutations in other cancer, complete loss of P53 is a frequent event in osteosarcoma (OS), the most common cancer of bone. The consequences of p53 loss for osteoblastic cells and OS development are poorly understood. Here we use murine OS models to demonstrate that elevated Pthlh (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 78 publications
(107 reference statements)
7
59
0
Order By: Relevance
“…To confirm PTHrP's autocrine/paracrine effect in Ocy454 cells, we assessed cAMP levels (with maximal phosphodiesterase inhibition) without adding exogenous PTHrP. In this way cAMP is generated only by autocrine receptor‐linked adenylyl cyclase activation by cell‐derived ligand(s) . Although Pthlh knockdown cells had higher Pth1r mRNA levels than vector control (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm PTHrP's autocrine/paracrine effect in Ocy454 cells, we assessed cAMP levels (with maximal phosphodiesterase inhibition) without adding exogenous PTHrP. In this way cAMP is generated only by autocrine receptor‐linked adenylyl cyclase activation by cell‐derived ligand(s) . Although Pthlh knockdown cells had higher Pth1r mRNA levels than vector control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because extracting sufficient protein from osteocytes purified from bone would not be feasible, we used overexpression of the murine Pthlh gene in the osteocyte cell line Ocy454 to characterize the PTHrP that they secrete. The biological assay measures PTHrP species containing intact N‐terminal protein (at least 34 residues), with a sensitivity of 0.01nM to 0.1nM . This showed PTHrP activity was retained in conditioned medium in cation exchange chromatography eluates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then used a reductionist system to address the requirement for the cAMP pathway, centered on PTHrP and CREB1 during the initiation of OS. Using primary long bone osteoblasts that could be engineered to become p53 deficient, we observed that these cells reproducibly underwent a hyper‐proliferative transformation at approximately 12‐14 days after deletion of p53 . The loss of p53 transcriptional activity was accompanied by activation of a cAMP gene signature.…”
Section: Murine Models Of Osmentioning
confidence: 99%
“…Recently, Walia et al demonstrated that normal osteoblasts survive depletion of both parathyroid hormone-related protein (PTHrP) and CREB1, whereas osteoblasts lacking p53 in OS depend on the continuous activation of the PTHrP-cAMP-CREB1 pathway. In the absence of PTHrP or CREB1, OS cells undergo proliferation arrest and apoptosis[111]. PTHrP and PTH are crucial regulators of bone formation and remodeling, and administration of high-dose human PTH increased incidence of OS in rats [112, 113].…”
Section: Driver-dependent Genetic Vulnerabilities As Targets Of Osmentioning
confidence: 99%